1984
DOI: 10.1073/pnas.81.10.3005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid internalization of the transferrin receptor in K562 cells is triggered by ligand binding or treatment with a phorbol ester.

Abstract: Treatment of human K562 cells with 4f3 phorbol 12-myristate 13-acetate (PMA) resulted in an approximately 50% reduction in cell surface transferrin receptors within 30-45 min as judged by binding of both ligand and antireceptor antibody. The affinity of the remaining surface receptors for diferric transferrin appeared to be unaltered. The time-dependent loss in transferrin receptors was also dependent upon PMA concentration, with a half-maximal effect observed at approximately 1 nM. The kinetic parameters for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
2
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(100 citation statements)
references
References 27 publications
9
88
2
1
Order By: Relevance
“…Subsequent decrease of the receptors on cell surface has been observed which could be responsible for the inhibition of cell growth by TPA treatment. Klausner et al reported that the decrease seemed to involve sequestering of the receptors to the inside of the cells during TPA treatment (18). However, no detailed study on the regulation of the receptors in TPA-treated cells has been done Here we report that the treatment of human erythroleukemia (K562) cells with TPA causes the decrease of transferrin receptors on the cell surface as well as in the cell interior.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Subsequent decrease of the receptors on cell surface has been observed which could be responsible for the inhibition of cell growth by TPA treatment. Klausner et al reported that the decrease seemed to involve sequestering of the receptors to the inside of the cells during TPA treatment (18). However, no detailed study on the regulation of the receptors in TPA-treated cells has been done Here we report that the treatment of human erythroleukemia (K562) cells with TPA causes the decrease of transferrin receptors on the cell surface as well as in the cell interior.…”
mentioning
confidence: 61%
“…It has also been observed that the phosphorylation of the transferrin receptor is markedly stimulated at that time (18,20,26). Subsequent decrease of the receptors on cell surface has been observed which could be responsible for the inhibition of cell growth by TPA treatment.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In HepG2 hepatoma cells (26) or in phorbol 12-myristate 13-acetate-treated K562 cells (27), the rate of iron uptake is almost twice as fast as that measured for transferrin. We propose that rapid recycling of transferrin through acidic sorting endosomes could account for the additional iron delivered to the cells, since a rapid recycling would have caused an underestimation of the rate of transferrin uptake.…”
Section: Discussionmentioning
confidence: 99%
“…PKC-mediated phosphorylation has been implicated in the internalization of numerous receptors including the EGFR, CD4, TfR, and the asialoglycoprotein receptor (ASGPR) (Klausner et al, 1984;McCaffrey et al, 1984;Beguinot et al, 1985;Fallon and Schwartz, 1988;Shin et al, 1991). It has been demonstrated that PKC phosphorylates the EGFR at T654 (Hunter et al, 1984).…”
Section: Introductionmentioning
confidence: 99%